Effectiveness of Local Biodiversity Action Plans to Identify Locally Rare and Endangered Fish in Scotland. (2nd January 2016) - Hooker, O.E.; Maitland, P.S.; Bean, C.W.; Adams, C.E.
Abstract: Biodiversity loss is an important environmental issue globally. Local Biodiversity Action Plans (LBAPs) provide an important conservation tool and should represent national priority species where they are present. Although much effort has gone in to developing LBAPs, their value as a conservation tool has been questioned. Here the effectiveness of the LBAP system to raise awareness of the freshwater fishes of national and international priority in Scotland is tested. Inclusion of freshwater fish in the LBAP suite was evaluated using current distribution data taken from available literature sources. Of the 25 examined LBAPs in Scotland, there were 79 LBAP entries for the 12 priority freshwater fishes found in Scotland. This contrasts with an expectation of 139 entries. Nineteen authorities failed to represent all priority freshwater fish species extant in their geographical boundary. Fourteen authorities provided cover for 50% or less for the species distributed in their area and five authorities included no rare freshwater fish species where one or more was expected. Possible underlying reasons for this mismatch include: frequently changing conservation status and taxonomic blindness of this group. It is plausible to suggest that this low rate of inclusion will have a detrimental effect on the allocation of limited conservation resources.